VD_FINDINFO Jug / 2016 / 88 vom 13. November 2015 - VD Tribunal cantonal (2015)
PROCÉDURE ÉCRITE, INDEMNITÉEN GÉNÉRAL, DÉPENS, FRAIS JUDICIAIRES | 406 al. 1 let. d CPP (CH), 426 al. 1 CPP (CH), 433 al. 1 CPP(CH)